VIRTUAL TARGET CONSTRUCTION FOR DISCOVERY OF HUMAN HISTAMINE H4 RECEPTOR LIGANDS EMPLOYING A STRUCTURE-BASED VIRTUAL SCREENING APPROACH - NUGRAHA, GERRY; PRANOWO, HARNO DWI; MUDASIR, MUDASIR; ISTYASTONO, ENADE PERDANA (International Journal of Applied Pharmaceutics, 2022)
Objective: This study aimed to construct a virtual target to be used in structure-based virtual screening (SBVS) campaigns to discover ligands for human histamine receptor H4 (hHRH4). Methods: The virtual targets construction was initiated by hHRH4 homology modeling, followed by molecular docking of seliforant to the homolog model, and the virtual target candidate was constructed. The hHRH4 complexed to seliforant was subjected to molecular dynamics (MD) simulations in 100 ns. Finally, the pose with the least free energy of binding from the MD simulations was selected for further validation through re-docking simulations. All simulations were conducted by using the YASARA-Structure program package. Results: This study resulted in one validated target for SBVS protocols development. All RMSD values in the internal validation in snapshot 519 molecular dynamics simulation results were less than 2 Å, and this hHRH4 homology model is valid as a virtual target in an SBVS protocol. Moreover, using the clusterization module on MD simulations analysis, ten different virtual targets were available for further utilization. Conclusion: Virtual targets resulted from this study offer more possibilities to construct SBVS protocols to identify hHRH4 ligands. The validated virtual target and the ten different virtual targets resulted from clusterization can be accessed in the following GitHub repository: https://github.com/nugrahagerry/hHRH4.